Virtual Reality Learning Electronics Laboratory - yuvina; Rezha Destiadi; Orli Binta Tumanggor (Politeknik Negeri Medan, 2021)
The changes that have hit the world in the 21st century have entered the era of the industrial revolution 4.0. The education sector will also be disrupted from the revolutionary era. The problems of various human activities in the world of education, such as ethics, will more or less affect the culture, direction, and progress of an organization. And the era of disruption can be seen from the development of information technology as a basis in human life. Many things have changed and become borderless with the use of unlimited computing power and data. Seeing the gap in the shift in national education, the Ministry of Education and Culture launched the Independent Learning Campus policy. Universities are expected to be able to answer the challenges of the Industrial 4.0 era through curriculum development by aligning technological literacy skills and human literacy. The method used is the Mix Method, qualitative and quantitative.